Judicial Appointments Commission: a comparison between the Judicial Appointments Commission in Malaysia and The Judicial Appointments Commission in United Kingdom / Ahmad Danial Mohd Azlan, Luqman Mazlan and Mohd Irzan Iswatt Mohd Noor - Mohd Azlan, Ahmad Danial; Mazlan, Luqman; Mohd Noor, Mohd Irzan Iswatt (2011)
This project paper has been conducted in relation of the Judicial Appointments Commission. For the purpose of our research, we have compared the two Acts which are the Judicial Appointments Act in Malaysia and also the Constitutional Reform Act in United Kingdom. This is because both models have different structures and functions as to having the exclusive rights towards judicial independence. In upholding the independence of Judiciary, we have done a comparison between these two countries, Malaysia and United Kingdom. This is important for the purpose of our paper project, in order to review the loopholes of structures and functions of Judicial Appointments Commission in Malaysia. This is because the setting up of this body defeats the purpose of having exclusive rights of judicial independence as there is still an infringement of power by the Executive solely by the Prime Minister. Furthermore, in order to provide a better form and structures of Judicial Appointments Commission, this project paper will provide a reasonable suggestions and rational recommendations on the loopholes discovered from the comparative study between the two bodies.